Gene editing monkeys: Retrospect and outlook - Liang, Weizheng; He, Junli; Mao, Chenyu; Yu, Chengwei; Meng, Qingxue; Xue, Jun; Wu, Xueliang; Li, Shanliang; Wang, Yukai; Yi, Hongyang (Frontiers in Cell and Developmental Biology, 2022)
Animal models play a key role in life science research, especially in the study of human disease pathogenesis and drug screening. Because of the closer proximity to humans in terms of genetic evolution, physiology, immunology, biochemistry, and pathology, nonhuman primates (NHPs) have outstanding advantages in model construction for disease mechanism study and drug development. In terms of animal model construction, gene editing technology has been widely applied to this area in recent years. This review will summarize the current progress in the establishment of NHPs using gene editing technology, which mainly focuses on rhesus and cynomolgus monkeys. Additionally, we will discuss the limiting factors in the applications of genetically modified NHP models as well as the possible solutions and improvements. Furthermore, we will highlight the prospects and challenges of the gene-edited NHP models.